Birth order, sibship size, and risk of atopic dermatitis, food allergy, and atopy: A systematic review and meta‐analysis - Daniil Lisik; Saliha Selin Özuygur Ermis; Athina Ioannidou; Gregorio Paolo Milani; Sungkutu Nyassi; Giulia Carla Immacolata Spolidoro; Hannu Kankaanranta; Emma Goksör; Göran Wennergren; Bright Ibeabughichi Nwaru (Clinical and Translational Allergy, 2023)
Abstract Background Atopic dermatitis and food allergy are two frequently concomitant manifestations of the presence of atopy. A substantial number of studies have been published on the association of birth order and sibship size (number of siblings) with atopic dermatitis, food allergy, and atopy. The present work is the first systematic synthesis of the existing literature on this topic. Methods Fifteen databases were searched. Screening, data extraction, and quality assessment were performed by independent pairs. Comparable numerical data were statistically synthesized using random‐effects robust variance estimation. Results In total, 114 studies were included out of 8819 papers obtained from database searches. Birth order ≥2 versus 1 was associated with lower risk of ever atopic dermatitis (pooled risk ratio [RR] 0.91, 95% CI 0.84–0.98), current food allergy (RR 0.77, 95% CI 0.66–0.90), and positive skin prick test (SPT) to common aeroallergens (RR 0.86, 95% CI 0.77–0.97). Sibship size ≥2 versus 1 was associated with decreased risk of current atopic dermatitis (RR 0.90, 95% CI 0.83–0.98), ever atopic dermatitis (RR 0.92, 95% CI 0.86–0.97), and positive SPT to common aeroallergens (RR 0.88, 95% CI 0.83–0.92). No putative associations were seen regarding atopy assessed through allergen‐specific immunoglobulin E with common allergens. Conclusion The presence of siblings and being second‐born or later may decrease the lifetime risk of atopic dermatitis and food allergy, albeit marginally. Similar association was seen with SPT sensitization. However, significant protection was not found for IgE sensitization.